Prescribing an annual plan for the competitive surf athlete: Optimal methods and barriers to implementation. - Bernards, J.; Blaisdell, R.; Light, T.; Stone, M. H. (Strength and Conditioning Journal, 2017)
As the sport of surfing continues to gain support, the need for a sound strength and conditioning program is paramount. With a season lasting upward of 8 months and traveling all over the world, programming for the sport of surfing quickly becomes a challenge. Therefore, the aim of this article is to provide a brief introduction into the technical and physiological aspects of the sport before providing a detailed annual plan the strength coach or surf athlete can modify for their own use.